Combination therapy of omalizumab with house dust mite immunotherapy in chronic spontaneous urticaria associated with sensitization to dust mites-case series - Kathuria, P C; Rai, Manisha (Indian Journal of Case Reports, 2021)
Chronic spontaneous urticaria (CSU) is a heterogeneous disorder with recurrent pruritic wheals and/or angioedema. The anti-immunoglobulin E (omalizumab) is used in CSU patients resistant to four-fold second-generation anti-histamines. Most clinical trials have experienced relapse after stopping omalizumab treatment. Here, we present a case series of five cases of chronic atopic urticarial concomitant allergic rhinitis and asthma which have shown immunologically significant positivity to Dermatophagoides pteronyssinus and Dermatophagoides farinae. Disease control was achieved (Urticaria Activity Score 7